Menakar Kembali Keberadaan Pelajaran Bahasa Indonesia Sebagai Ilmu Pengetahuan Di Sekolah Dasar - Minahul Mubin (Universitas Islam Lamongan, 2017)
Abstract: Indonesia language is an important part of education. Besides to be indonesia science, indonesia language becomes a long history. A long history of Indonesia language is started as nation’s official and unitary languange. In 1928, as a burning spirit to grab independence, which has written in constitution 1945, from sequece of long history and pass the prosess of perfectingso that indonesia language becomes important thing as science today.In this case, to reinstate the position of Indonesia language to its fungtion and benefit, in order not to scrapped into this period that can make our children away from their identity. In fact, there will be polarization concerning with existence of Indonesia language, either using 2013 curriculum or not. Essentially, by virtue of, is Indonesia languange presented as Indonesia science or literature linguist which in practice 2013 curriculum in fact not giving art value in literature.The nature of Indonesia language is a science which must be given to students to educate how to communicate well. This communication can be done either oral or written, all of those is to understand and respond local situation, regional, national, and global. This is one of reason why Indonesia languange must be educated in all education level, especially in elemantry school because it is a foundation in all lessons.Keywords: Mete Out, Indonesia Language, Science